Portrayal of Village Life in Transition: A Study of Kamala Markandaya’s Nectar in a Sieve - Gopalbhai Nagabhai Chhatrodiya (Vidhyayana - An International Multidisciplinary Peer-Reviewed E-Journal - ISSN 2454-8596, 2020)
Kamala Markandaya holds a reputed position in the field of Indian English Fiction. As a keen and conscious observer of society, she artistically shares her life experiences in her creative expressions. Her novels are full of varieties and present broad perspective of life. Her novels are based on east west conflicts, feminist issues and depict real characters who are victim of social evils. As a great story teller, Markandaya unfolds mysteries and realities of life in a comprehensive manner. Markandaya started writing novels after India’s Independence in which she addressed various issues. Nectar in a Sieve is her first published novel which captures the changing scenario of Post-Independence India. In the novel, Markandaya has painted realistic picture of Indian rural life and highlighted the social, economic and cultural problems of people during the transition period after the freedom. The present paper aims to study the novel Nectar in a Sieve in which Markandaya has depicted rural life in the transition period.